THE DESCRIPTION OF NATIONAL SPIRIT IN CHILDREN'S LITERATURE ON EXAMPLE OF MARK TWAIN`S NOVEL “THE ADVENTURES OF TOM SAWYER” (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article describes the image of the national psyche in children's fiction, explores aspects that glorify nationality, and discusses the importance of national mentality in children's literature on the example of Mark Twain's "The Adventures of Tom Sawyer" in which the character traits of artistic characters are analyzed and the aspects that reflect the national spirit are highlighted.